CHRISTIAN MISSIONS AND COLONIAL RULE IN AFRICA: OBJECTIVE AND CONTEMPORARY ANALYSIS - Okon, Etim E. (European Scientific Journal, ESJ, 2014)
The purpose of this paper is to determine the correlation between the nineteenth century missionary enterprise and colonial occupation of Africa. European missionaries entered Africa simultaneously at the very beginning of colonial conquest and domination of Africa. What was the relationship between missionaries, traders and administrators in the colonial era? What can we identify as the predetermined objective of colonialism vis-a-vis missions in Africa? These are some of the questions that the present study will attempt to answer from the perspective of the historiography of European expansion in Africa.